Cockayne syndrome group A and ferrochelatase finely tune ribosomal gene transcription and its response to UV irradiation. Issue 19 (28th September 2021) - Lanzafame, Manuela; Branca, Giulia; Landi, Claudia; Qiang, Mingyue; Vaz, Bruno; Nardo, Tiziana; Ferri, Debora; Mura, Manuela; Iben, Sebastian; Stefanini, Miria; Peverali, Fiorenzo A; Bini, Luca; et al.
Abstract: CSA and CSB proteins are key players in transcription-coupled nucleotide excision repair (TC-NER) pathway that removes UV-induced DNA lesions from the transcribed strands of expressed genes. Additionally, CS proteins play relevant but still elusive roles in other cellular pathways whose alteration may explain neurodegeneration and progeroid features in Cockayne syndrome (CS). Here we identify a CS-containing chromatin-associated protein complex that modulates rRNA transcription. Besides RNA polymerase I (RNAP1) and specific ribosomal proteins (RPs), the complex includes ferrochelatase (FECH), a well-known mitochondrial enzyme whose deficiency causes erythropoietic protoporphyria (EPP). Impairment of either CSA or FECH functionality leads to reduced RNAP1 occupancy on rDNA promoter that is associated to reduced 47S pre-rRNA transcription. In addition, reduced FECH expression leads to an abnormal accumulation of 18S rRNA that in primary dermal fibroblasts from CS and EPP patients results in opposed rRNA amounts. After cell irradiation with UV light, CSA triggers the dissociation of the CSA–FECH–CSB–RNAP1–RPs complex from the chromatin while it stabilizes its binding to FECH. Besides disclosing a function for FECH within nucleoli, this study sheds light on the still unknown mechanisms through which CSA modulates rRNA transcription. Graphical Abstract: